Impacts of post‐radiotherapy lymphocyte count on progression‐free and overall survival in patients with stage III lung cancer. Issue 11 (21st September 2020) - Matiello, Juliana; Dal Pra, Alan; Zardo, Laise; Silva, Ricardo; Berton, Danilo C
Abstract : Background: We evaluated the impact of thoracic radiation in patients with non‐small cell lung cancer (NSCLC), considering the depletion of total lymphocytes, use or not of chemotherapy, and radiation doses in healthy lung tissue. Methods: Patients with stage III NSCLC, ECOG 0 to 2, receiving radiotherapy with or without chemotherapy were prospectively evaluated. All patients should be treated with three‐dimensional radiotherapy and received biologically effective doses (BED10α/β 10) of 48 to 80 Gy. Peripheral blood lymphocyte total counts were measured at the start of radiotherapy and at 2, 6 and 12 months after radiotherapy. Along with lymphocytes, PTV and doses of 5 Gy and 20 Gy in healthy lung tissue were also evaluated as potential factors influencing overall survival (OS) and progression‐free survival (PFS). Results: A total of 46 patients were prospectively evaluated from April 2016 to August 2019, with a median follow‐up of 13 months (interquartile range, 1–39 months). The median of OS of all cohort was 22, 8 months (IC 95% 17, 6–28, 1) and the median PFS was 19, 5 months (IC 95%: 14, 7–24, 2). Most patients received concurrent or neoadjuvant chemotherapy (43; 93.4%). No patient received adjuvant immunotherapy. The lower the lymphocyte loss at 6 months after radiotherapy (every 100 lymphocytes/mcL), the greater the chance of PFS (HR, 0.44; 95%CI, 0.25–0.77; P = 0.004) and OS (HR, 0.83; 95%CI, 0.70–0.98; P = 0.025; P = 0.025). BED was a protective factor for both PFS (HR, 0.52; 95%CI 0.33–0.83; P = 0.0006) and OS (HR, 0.73; 95%CI 0.54–0.97; P = 0.029). Conclusions: Our results suggest that lymphocyte depletion after radiotherapy reduces tumor control and survival in patients with stage III lung cancer. Radiation doses equal or higher than 60 Gy (BED10 72 Gy) improve PFS and OS, but they negatively affect lymphocyte counts for months, which reduces survival and the potential of immunotherapy. Key points: Significant findings of the study: Thoracic irradiation for locally advanced lung cancer depletes T lymphocytes for months. Patients whose lymphocyte loss is lower have better overall survival and progression‐free survival. What this study adds: It is necessary to protect the lymphocyte population, as well as other organs at risk. New forms of irradiation for large fields are needed. Furthermore, could immunotherapy before chemo‐radiotherapy, with a greater number of lymphocytes, bring an even better result? Abstract : Radiation therapy is an essential local treatment for locally advanced lung cancer; however, the large fields of irradiation may have collateral effects. We revealed that lymphocyte counts decrease for a long time after irradiation, worsening OS and PFS. The other important issue is that low lymphocyte counts may affect the potential of immunotherapy. Immunotherapy at different time points and use of smaller radiation fields with high doses may be key issues for the future of lung cancer treatment.